Significant pulmonary disease burden in treatment resistant disseminated cryptococcal infection: A case report - Viswanathan Shanthakumar, Shanthi; Tai, Mei Ling Sharon; Rais Sanusi, Abdul; Sivalingam, Sivakumar; Zakai, Saad Bader (Springer Verlag, 2017)
Cryptococcus neoformans causes severe disseminated infection in immunocompromised individuals. We report a case of an immunocompetent adult male who presented with treatment-resistant central nervous system manifestations and significant pulmonary disease burden. Hematology and lumbar puncture were positive, aided by computerized tomography-guided histological confirmation. Despite medical therapy, there was inadequate resolution, and surgical resection was performed. On follow-up, investigations showed complete resolution, and the patient has remained disease-free at 5 years. This highlights the importance of looking for other sites in resistant cryptococcal meningitis and the value of cardiothoracic intervention for slowly resolving pulmonary cryptococcomas.